Analisis Anarkisme Remaja dalam Kejahatan Klitih di Kabupaten Bantul: Faktor, Karakteristik, dan Upaya Penegakan Hukum - Pamuji, Ryan Satria (Proceedings Series on Social Sciences & Humanities, 2024)
The phenomenon of street violence that occurs in Bantul Regency, Yogyakarta, namely klitih, is a serious concern for the local community. This research aims to analyze the factors that influence juvenile involvement in crime, characteristics of perpetrators, crime patterns, and efforts to increase the effectiveness of law enforcement in dealing with these problems. The research method used is a normative approach with a qualitative descriptive approach. Secondary data was obtained from various literary sources and related legal documents. The results of the research show that social factors, the search for identity, hereditary school gangs, family, education, environment, as well as the influence of media and technology play a role in teenagers' involvement in klitih. The characteristics of the perpetrators include teenagers aged between 15 and 20 years, low educational background and a dysfunctional family environment. The klitih crime pattern involves acts of violence with the aim of showing courage in front of a peer group. Efforts to increase the effectiveness of law enforcement include improving coordination between law enforcement agencies, increasing security patrols, utilizing technology, and implementing comprehensive rehabilitation programs.